The role of mentalizing in the relationship between schizotypal personality traits and state signs of psychosis risk captured by cognitive and perceptive basic symptoms - Salaminios, George; Sprüngli-Toffel, Elodie; Michel, Chantal; Morosan, Larisa; Eliez, Stephan; Armando, Marco; Fonseca-Pedrero, Eduardo; Derome, Melodie; Schultze-Lutter, Frauke; Debbané, Martin (Frontiers in Psychiatry, 2023)
Objective: Schizotypal traits and disturbances in mentalizing (the capacity to understand the mental states driving one's own and others' behaviours) have been implicated in increased vulnerability for psychosis. Therefore, we explored the associations linking schizotypal traits, mentalizing difficulties and their interactions to clinical high-risk for psychosis (CHR-P), as captured by the Basic Symptoms (BS) approach, during adolescence and young adulthood. Method: Eighty-seven adolescents and young adults from the general population (46% male, 44% female; age: 14-23 years) were assessed with the Schizophrenia Proneness Interview (SPI-CY/A) for eleven perceptive and cognitive BS, with the Schizotypal Personality Questionnaire (SPQ) for schizotypal traits, and with the Reflective Functioning (RFQ) Questionnaire for selfreported mentalizing abilities. The RFQ evaluates the level of certainty (RFQc scale) and uncertainty (RFQu scale) with which individuals use mental state information to explain their own and others' behaviours. Results: Logistic regression models showed significant positive effects of the SPQ disorganization scale on perceptive BS and of the SPQ interpersonal scale on cognitive BS. Post-hoc analyses revealed that schizotypal features pertaining to odd speech and social anxiety, respectively, were associated with perceptive and cognitive BS. Furthermore, higher scores on the RFQu scale and lower scores on the RFQc scale independently explained the presence of cognitive BS. Finally, significant interaction effects between RFQc and SPQ odd speech on perceptive BS, and between RFQc and SPQ social anxiety on cognitive BS were found. Conclusion: Our findings suggest that schizotypal traits and mentalizing significantly relate both independently and through their interactions to the presence of cognitive and perceptive BS included in CHR-P criteria. Furthermore, mentalizing dysfunction may contribute in the relation between schizotypal traits and early state signs of CHR-P. Mentalizing may support both detection and early treatment of CHR-P among adolescents and young adults who present with trait risk for psychosis.